Conservation of Neisseria gonorrhoeae pilus expression regulatory genes pilA and pilB in the genus Neisseria. - Taha, M K (1990)
The pili of Neisseria gonorrhoeae mediate bacterial adhesion to the host-susceptible tissues. We have previously reported the identification of two genes, pilA and pilB, which act in trans to regulate pilus expression. Besides this regulatory function, pilA participates in an essential function for bacterial viability. Here we show that pilA and pilB homologs are also present in a variety of other members of the Neisseriaceae family of bacteria in contrast to the gonococcal pilin gene which hybridizes only to the pathogenic Neisseria species.